Holy of the plant when the arabs befor islam - عبود سمار, سعد; abood sammar, saad (Journal of College of Education, 2019)
The study sheds light on "the sacred of plants in the Arabs before Islam." The talk begins with the introduction of the main ideas of the research, with a brief presentation of the homologues of the plant sanctuary in the ancient Near Eastern beliefs of Mesopotamia and the Arabs before Islam. In the discussion we discussed the substitution of the gods into the trees, then the symbols of the plant gods, and the religious rituals to increase the agricultural yield, and we referred to the religious value of some plants